2015
DOI: 10.1002/ccd.25988
|View full text |Cite
|
Sign up to set email alerts
|

The requirement of extracorporeal circulation system for transluminal aortic valve replacement: Do we really need it in the catheterization laboratory?

Abstract: Transcatheter aortic valve replacement (TAVR) is the mainstay for treating high-risk patients with aortic stenosis. As the TAVR procedures worldwide keep increasing, it is inevitable that more issues and complications will arise. Such a complication that merits attention is the conversion of TAVR into open-heart surgery and the necessity this complication creates to have an extracorporeal circulation system in the catheterization laboratory. This review contains an analysis of all major randomized trials and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Due to the improvements in device technology, technique, and success rates, TAVR has evolved into a relatively low‐risk procedure despite the high comorbidity and relative frailty of patients needing this procedure 18. As noted in a recent article, less than 5% of all TAVR procedures require conversion to open surgery, making this procedure both safe and feasible in high‐risk populations 19. However, in patients presenting with concomitant cardiogenic shock, TAVR is associated with nearly 33% 30‐day and 60% 1‐year mortality 20.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the improvements in device technology, technique, and success rates, TAVR has evolved into a relatively low‐risk procedure despite the high comorbidity and relative frailty of patients needing this procedure 18. As noted in a recent article, less than 5% of all TAVR procedures require conversion to open surgery, making this procedure both safe and feasible in high‐risk populations 19. However, in patients presenting with concomitant cardiogenic shock, TAVR is associated with nearly 33% 30‐day and 60% 1‐year mortality 20.…”
Section: Discussionmentioning
confidence: 99%
“…However, severe complications requiring sternotomy still occur in about 1–2.8% and are associated with an increase in 30‐day mortality of up to 45% . With decreasing complication rates, the necessity for a multidisciplinary heart team and stand‐by circulatory support has been challenged by some , while others have highlighted the importance . In this study, we observed a steep decline in the need of emergency vaECMO during a 6‐year period from 9.3% in 2010 to 0.9% in 2015, indicating a substantial reduction in life‐threatening complications with increasing experience and iteration of devices.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, with greater experience and better success rates, TAVI has become feasible and is increasingly used in very high-risk patients. 20 Proper preparation before dangerous procedures with maximal prophylactic support may assist in the success of the intervention and improve patient outcomes. On the other hand, pMCSs are expensive, not always available, and may be associated with inherent complications.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, unpredicted complications may occur, and a backup strategy should be available to prevent imminent death during acute, life‐threatening hemodynamic collapse. Moreover, with greater experience and better success rates, TAVI has become feasible and is increasingly used in very high‐risk patients 20 . Proper preparation before dangerous procedures with maximal prophylactic support may assist in the success of the intervention and improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%